The Chicago manual of style. (The University of Chicago Press, 2010)
This reference work provides information on manuscript preparation, punctuation, spelling, quotations, captions, tables, abbreviations, references, bibliographies, notes, and indexes, with sections on journals and electronic media. This 16th edition has been revised to reflect how publishing professionals work in the digital age; it provides new information and guidelines for electronic workflow and processes.